The dyscalculia toolkit : supporting learning difficulties in maths - Bird, Ronit (Los Angeles : Sage, 2017)
This book helps teachers and parents support learners with dyscalculia or those struggling with mathematics and includes editable pupil tracking sheets organized by teaching point and section, 10 videos with over 45 minutes of material demonstrating a selection of games from every section, and over 200 activities and 50 games.--
Previous edition published 2013.
Includes index.
Keywords: Acalculia in children; Acalculia -- Patients -- Education; Mathematics -- Study and teaching -- Activity programs; Special education -- Mathematics; Special education -- Activity programs